2016
DOI: 10.5152/ucd.2015.3086
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic partial cholecystectomy: A safe and effective alternative surgical technique in "difficult cholecystectomies"

Abstract: Objective: Laparoscopic cholecystectomy has become the ''gold standard'' for benign gallbladder diseases due to its advantages. In the presence of inflammation or fibrosis, the risk of bleeding and bile duct injury is increased during dissection. Laparoscopic partial cholecystectomy (LPC) is a feasible and safe method to prevent bile duct injuries and decrease the conversion (to open cholecystectomy) rates in difficult cholecystectomies where anatomical structures could not be demonstrated clearly. Material an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 38 publications
1
19
0
3
Order By: Relevance
“…It is well-known that less post-operative pain and rapid improvement in physical activity are the most important advantages of minimally invasive surgery [1]. Nevertheless, many patients suffer from significant pain after laparoscopic abdominal surgeries [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that less post-operative pain and rapid improvement in physical activity are the most important advantages of minimally invasive surgery [1]. Nevertheless, many patients suffer from significant pain after laparoscopic abdominal surgeries [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Experienced surgeons may feel comfortable performing damage-control procedures laparoscopically (12).…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review and meta-analysis, it was reported that partial cholecystectomy resulted in lower rates of common bile duct injury, but more frequent postoperative minor complications in difficult cholecystectomies. [6] Kulen et al [21] analyzed the data of 80 patients with cholelithiasis who underwent LPC (n=40) and conversion cholecystectomy (n=40). The authors reported that no patients in the LPC group suffered from late complications; however, the rate of late complications was 32.5% in the conversion cholecystectomy group.…”
Section: Discussionmentioning
confidence: 99%
“…Subhepatic collection, biliary fistula, and residual bile duct stones constituted the most frequent complications after LPC. [6,21] Palliative or minimally invasive techniques such as percutaneous drainage and ERCP are the most efficient treatments for such complications following LPC. [22] The incidence of postoperative ERCP after LPC was reported as 4.1%, and the most common indications for ERCP after LPC were retained stones (59%) and bile leakage (31.5%).…”
Section: Discussionmentioning
confidence: 99%